1994
DOI: 10.1093/nar/22.22.4810
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of oligodeoxyribonucleotide—polyethylene glycol conjugates

Abstract: Pools of oligonucleotide conjugates consisting of 10-400 different molecular species were synthesized. The conjugates contained a varying number of ethylene glycol units attached to 3'-terminal, 5'-terminal and internal positions of the oligonucleotides. Conjugate synthesis was performed by phosphoramidite solid phase chemistry using suitably protected polyethylene glycol phosphoramidites and PEG-derivatized solid supports containing polydisperse PEGs of various molecular weight ranges. The pools were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
(26 reference statements)
2
70
0
Order By: Relevance
“…PEG can be introduced to an ODN at the 3' end or 5' end or internal positions in the solid-phase synthesis of ODNs (488)(489)(490). However, these synthesis strategies do not allow easy upscaling.…”
Section: 32mentioning
confidence: 99%
See 2 more Smart Citations
“…PEG can be introduced to an ODN at the 3' end or 5' end or internal positions in the solid-phase synthesis of ODNs (488)(489)(490). However, these synthesis strategies do not allow easy upscaling.…”
Section: 32mentioning
confidence: 99%
“…PEG coupling to both the 3' and 5' terminal positions of an antisense ODN produced more than 10-fold increase in exonuclease stability, while having no effect on the ability of hybridization (488). Furthermore, the cellular uptake of ODNs can also benefit from PEGylation (496).…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they can sterically shield molecules encapsulated in drug carriers and thus have been covalently or noncovalently conjugated to a number of pharmaceuticals, a process called PEGylation [1,2]. These biomedical applications of PEGylation have been shown to reduce the cytotoxicity as well as increase the water solubility and circulating lifetime of drug molecules or drug carriers such as peptides [3,4], oligonucleotides [5][6][7][8], lipid liposomes [9][10][11][12][13], biodegradable hydrogels [14,15] and nanoparticles [16][17][18][19]. Although experiments have revealed vital information on the large-scale interactions of PEGs with drugs and drug carriers, many atomic-level questions that cannot be answered by experiments remain to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are conjugates with cationic compounds, such as poly-(L)-lysine 9 or polyamides, 10 lipophilic conjugates, such as cholesterol, 11 long chain alcohols, 12 phospholipids, 13 aromatic compounds, 14 as well as polyethylene glycol. 15 Furthermore, the effect of attachment of these compounds at different position of the oligonucleotides including the bases, the backbone and the 3 ' -or 5 ' end was investigated. Uekama and coworkers reported that gene transfer activity was significantly improved by conjugates of α-, β-, and γ-cyclodextrins with polyamidoamine starburst dendrimers.…”
mentioning
confidence: 99%